2004
DOI: 10.1007/s00441-004-0979-2
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalisation of P2X and P2Y nucleotide receptors in the rat nasal mucosa

Abstract: Purinoceptor subtypes were localised to various tissue types present within the nasal cavity of the rat, using immunohistochemical methods. P2X3 receptor immunoreactivity was localised in the primary olfactory neurones located both in the olfactory epithelium and vomeronasal organs (VNO) and also on subepithelial nerve fibres in the respiratory region. P2X5 receptor immunoreactivity was found in the squamous, respiratory and olfactory epithelial cells of the rat nasal mucosa. P2X7 receptor immunoreactivity was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 46 publications
1
29
1
Order By: Relevance
“…Most relevant to this study, purinergic nucleotides have been found to reduce odor responsiveness in cultured mouse OSNs (25). In addition, the expression of the purinergic receptor subtypes P2Y 1 R and P2Y 2 R has previously been characterized in olfactory epithelium (25,50) consistent with our findings in the current study. Thus, the present data, taken together with previous findings, suggest that purinergic receptors in vivo may associate with certain ORs, such as M71, to promote OR surface expression and regulate OR functionality.…”
Section: Discussionsupporting
confidence: 91%
“…Most relevant to this study, purinergic nucleotides have been found to reduce odor responsiveness in cultured mouse OSNs (25). In addition, the expression of the purinergic receptor subtypes P2Y 1 R and P2Y 2 R has previously been characterized in olfactory epithelium (25,50) consistent with our findings in the current study. Thus, the present data, taken together with previous findings, suggest that purinergic receptors in vivo may associate with certain ORs, such as M71, to promote OR surface expression and regulate OR functionality.…”
Section: Discussionsupporting
confidence: 91%
“…Model simulations accurately predicted the predominant role of the low affinity group in the regulation of high ATP concentrations (Ͼ1 M) (43)(44)(45)(46), as demonstrated on HBE cultures using selective inhibitors of NSAP (10 mM levamisole) (13) and NTPDase 3 (10 M NF-279) (53). Therapies inhibiting these ectoenzymes could potentially accentuate airway epithelial apoptosis (65,66) and inflammatory responses (45) because of increased ATP-mediated activation of P2X 7 receptors, which are up-regulated in lung diseases (67). In addition, these enzymes are likely responsible for the rapid elimination of aerosolized nucleotides (1-100 M) used to diagnose asthma and chronic obstructive pulmonary disease (ATP and AMP) (47,48), for the treatment of CF and primary ciliary dyskinesia (UTP) (49 -52) and in animal studies (48,68,69).…”
Section: Discussionmentioning
confidence: 99%
“…RT-PCR studies of human nasal epithelial cells showed expression of mRNA for P2X3, P2X4, P2X7, P2Y 1 , P2Y 2 , P2Y 4 , P2Y 6 , P2Y 11 , and P2Y 12 , and functional studies showed that luminal membranes express P2Y 2 , P2Y 6 , and probably P2Y 11 receptors, whereas basolateral membranes express P2Y 2 receptors; P2X3, P2X4, P2X7, P2Y 4 , and P2Y 12 did not seem to be functional in normal epithelial cells (Kim et al, 2004). Immunohistochemical studies of P2 receptor proteins showed P2X3 receptors on neurons of the rat nasal mucosa, P2X5 and P2X7 receptors on respiratory epithelial cells, P2Y 1 receptors on respiratory epithelial cells and submucosal glands, and P2Y 2 receptors on mucous secretory cells (Gayle and Burnstock, 2005). Zinc increased ciliary beat frequency in a calcium-dependent way in mouse nasal septal epithelial cultures through activation of P2X receptors and may thus be a useful agent for stimulating mucociliary clearance (Woodworth et al, 2010).…”
Section: Nasal Mucosamentioning
confidence: 94%